The International Court of Justice and the international humanitarian law rules for armed conflicts - Arevalo-Ramírez, Walter (Revista científica "General José María Córdova.", 2022)
This article analyzes the undermined importance of the International Court of Justice’s (ICJ) case law in interpreting international humanitarian law (IHL) and its relationship with public international law. It examines how the ICJ has elevated IHL to customary law, declaring it “intransgressible” and equating it with jus cogens, and identified particular obligations for the parties in conflict. The article studies how the Court has clarified the relationships between customary IHL with the law of treaties and has declared which elements of IHL constitute the most basic principles of humanity, applicable whether it is an international or non-international armed conflict. Finally, the text analyzes how the Court, has discouraged counterproductive separations between the application of IHL and international human rights law.